The Relationship Between Oral Health-Related Quality of Life and Oral Halitosis in Patients Undergoing Splinting Therapy - Nuzulul ismi; Sunnati Sunnati; Maida Fitri (FKG Universitas Syiah Kuala, 2024)
Periodontitis is one of the primary causes of tooth mobility, pain, and irreversible inflammation in the supporting tissues of the teeth. Comprehensive management of periodontitis cases with tooth unsteadiness often involves splinting therapy before progressing to advanced treatment phases. However, this condition facilitates the formation of plaque in the oral cavity, which is one of the causes of halitosis and impact quality of life related to oral health. This study aimed to determine the relationship between oral health-related quality of life and halitosis in patients undergoing splinting therapy.This research employed an analytic study with cross sectional design. Data were collected using the OHIP-14 questionnaire from 31 periodontitis patients who had received splinting therapy, followed by a halitosis examination. The data were analyzed using Spearman's correlation test. This study revealed that 25 people (80.6%) had a good quality of life, 5 people (16.1%) had a moderate quality of life, and 1 person (3.2%) had a poor quality of life. The condition of halitosis was found in 13 subjects who were associated with oral-health related quality of life in patients undergoing splinting therapy with a p-value of 0.05. It can be concluded that statistically there is no relationship between oral-health related quality of life and halitosis in patients receiving splinting therapy.